Analisis Konseling Multikultural sebagai Upaya Mencegah Diskriminasi Antar Siswa di Lingkungan Sekolah - Leppriani Lolok; Afnisela Palloan; Bittoen, Bittoen; Enjelina Markus Richard; Ronaldo Stefanus (Aljabar : Jurnal Ilmuan Pendidikan, Matematika dan Kebumian, 2025)
This study highlights the importance of understanding the cultural, religious, and social diversity present in every student. Multicultural counseling is viewed as an approach that helps counselors grasp the dynamics of student interactions and identify potential discriminatory behaviors. The discussion covers common forms of discrimination in schools, including stereotypes, identity-based bullying, and social exclusion. The study also emphasizes the strategic role of counselors in providing interventions through individual counseling, group counseling, and preventive programs focused on strengthening empathy and tolerance. The implementation of multicultural counseling programs is presented as a concrete effort to build an inclusive school climate. The findings show that this approach is effective in reducing conflict, increasing cross-cultural awareness, and fostering healthier social relationships among students. This research also highlights the importance of the school counselor's role in creating a safe and inclusive environment. Counselors can conduct needs assessments to identify patterns of discrimination and provide appropriate interventions. In addition, collaboration with teachers, parents, and the school is also needed to create effective prevention programs. This program is expected to have a positive impact on students and create a school culture that is more just and respects differences